Social Work as a Product and Project of Whiteness, 1607–1900. Issue 1 (2nd January 2021) - Gregory, Joshua R.
ABSTRACT: Whiteness is a distinctive feature of historical and contemporary social work. Consequently, histories of social work do not reflect this fact; for a defining quality of whiteness is that it does not readily identify or critique itself. In keeping with its mission of social justice and obligation of critical self-reflection, however, social work faces the imperative of reckoning with its own whiteness. For lack of acknowledgment of the whiteness that characterizes the profession, social work exhibits theoretical shortcomings and practical incongruences, and lapses into a misrepresentation of its own history that compromises the authenticity of its ostensible identity and mission. The present article begins with the settlement of the first Anglo-American colony and proceeds to the turn of the nineteenth century, mapping the symbiotic evolutions of whiteness and social work, which demonstrate social work to be, in many ways, a product and project of whiteness. This article utilizes historical and historiographical analysis to exemplify a model for constructing counter-narratives that subvert the normative boundaries of hegemonic whiteness that constrain traditional social work histories.